1970
DOI: 10.3126/jnps.v30i1.2455
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Condoms among Adolescents in Kathmandu Valley

Abstract: Introduction: The issues of sexual and reproductive health (SRH) remain the leading cause of ill health among adolescents worldwide and are of growing concern in Nepal. The correct knowledge of condoms is integral part of SRH. The present study was carried out to assess and compare the knowledge about condoms among adolescents in the Kathmandu valley of Nepal. Aim: To study, assess and compare the knowledge about condoms among adolescents in the Kathmandu valley of Nepal. Methods: The study was a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…However, many Nepalese young people lack such skills. Jha and colleagues found that many young people in Nepal lack the power and skills to use sexual and reproductive health services ( 8 ). Hence, programme designers should also focus on developing negotiation skills in young people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many Nepalese young people lack such skills. Jha and colleagues found that many young people in Nepal lack the power and skills to use sexual and reproductive health services ( 8 ). Hence, programme designers should also focus on developing negotiation skills in young people.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Nepal have documented that knowledge about sexual and reproductive health, particularly about STIs and condoms, is inadequate and that knowledge among male and urban young people was generally better than females and rural young people ( 8 , 9 , 65 ). Poor knowledge about many aspects of sexual health is unlikely to encourage the use of sexual and reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sexual maturation or puberty go hand in hand with the physical growth of the adolescents leading to intimate relationships at an early age in case of inappropriate guidance and incomplete information. It thus, becomes important to promote sexual literacy, wherein sex education can contribute to positive psychosocial development and well-being throughout adolescence and adulthood [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual behaviour of young people is one of the public health issues (WHO, 2011). Sexual and reproductive health issues remain the leading cause of ill-health among young people (Jha, Chaurasia, & Jha, 2010). Premarital sex has been widely accepted, especially in Western countries, where two-thirds of young people have had sexual intercourse during their teens (UNICEF, 2001).…”
Section: Introductionmentioning
confidence: 99%